POTENSI EKOWISATA SUNGAI KLAOGIN DI KAMPUNG KLAOGIN, DISTRIK SEREMUK, KABUPATEN SORONG SELATAN, PROVINSI PAPUA BARAT DAYA - Tri Berta Br Tarigan; Henderina Lellotery; Husein Marasabessy (Jurnal Sylva Scienteae, 2026)
This study aims to identify and analyze the ecotourism potential of the Klaogin River area in Klaogin Village, Seremuk District, South Sorong Regency, Southwest Papua Province. A qualitative descriptive approach supported by quantitative data was employed through field observation, in-depth interviews, Focus Group Discussion, and documentation studies. Results reveal diverse and high-quality ecotourism potential: the Klaogin River with clear water and intact riparian vegetation; the Klaogin Waterfall as a sacred cultural and ecological site; a traditional shrimp fishing spot rooted in indigenous knowledge; and rich biodiversity of 17 flora species (including two protected species: Myristica teysmannii and Agathis dammara) and 40 bird species dominated by parrots and cockatoos. Cultural potential is reinforced by sacred sites, the traditional Lahan Kla/Se water management system, customary conservation rules (sasi), and traditional dances. Road access is available from Sorong via Teminabuan, with basic facilities including gazebos, toilets, traditional boats, and a community homestay. Klaogin River holds strong potential as a community-based ecotourism destination, provided conservation principles are maintained and community involvement is strengthened.